Thinking architecturally : lead technical change within your engineering team - Schutta, Nathaniel T. (O'Reilly Media, 2018)
New software technology appears every year. Like clockwork, another language, library, pattern, or approach will arrive on the scene with plenty of hype and developer enthusiasm. As someone whose job requires making architectural decisions, you need to evaluate these new technologies with an eye toward the inevitable trade-offs before deciding if a new framework or language is right for your project. In this ebook, solution architect Nathaniel Schutta guides tech leads, practicing architects, and both senior and junior developers through the process of appraising promising new technologies. Recognizing how today's tech is informed by the past is a key part--some approaches that didn't work years ago might now have all the ingredients to succeed. You'll learn how to make effective decisions regarding the use of new tech solutions and explore the value of fitness functions to ensure that your ultimate choice is reflected in the codebase. Get guidelines, techniques, and advice for evaluating new tools and technologies Determine the unique needs of your project before deciding which technology to use Examine the codebase, documentation, testability, and other criteria when evaluating new tools Learn approaches for introducing new technology to skeptical people in your company and on your team Manage the quality attributes of your system once new technology is introduced Learn practical techniques to stay current in an ever-evolving industry.